The Situation of Youth on the European Labour Markets – Econometric Analyses - Bal-Domańska, Beata (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The phenomenon of low professional activity of young people, especially those not in employment, education or training represents an important element of socio‑economic policy considered on the global forum. The Reports covering the problem of youth on labour markets are highlighting the difficult situation in this respect in many countries worldwide. The situation of youth on the markets in individual EU countries is strongly diversified, e.g. in terms of time of starting professional activity. The purpose of the paper is the classification of European labour markets according to the characteristics of the situation of young people. The cluster methods for analysis of youth labour markets diversification have been conducted, and econometric models have been used to assess the relations between the employment rate among youth and the part‑time agreements popularity.